Developmental Effects of Davydov’s Mathematics Curriculum in Relation to School Readiness Level and Teacher Experience - Sidneva, Anastasia (Frontiers in Psychology, 2020)
Davydov’s mathematics curriculum was designed according to the principles of the Cultural Historical Activity Approach (CHAT). In this study we analyzed some developmental effects of its realization in Grade One (N=43, two classes), in relation to the children’s school readiness level (specifically, their motivation and voluntary regulation), and their teacher's experience (a very experienced teacher in one class, and a less experienced one in the other). We assessed two groups of developmental effects: 1) some general math abilities (comparison of objects, measurement and ability to solve simple problems of addition and subtraction; and 2) some abilities, which are very specific to Davydov’s mathematics curriculum (i.e., the ability to put numbers on a number line and to measure quantity using different measures). At the beginning of the Grade One, we divided all participants into three groups according to their level of motivation (low, medium, or high), voluntary regulation (low, medium, or high) and logical preservation (low, medium, or high) in terms of J.Piaget. After one year (at the beginning of Grade Two) we measured general effects again and also measured specific effects. The results showed that all the children became significantly better in all general math abilities. It was also found that progress in math abilities does not depend on the initial level of school readiness of children. Children with different levels of voluntary regulation, motivational readiness, and the level of logical preservation show improvements in general math abilities. As for the mathematical skills specific to the Davydov’ program, the achieved level of their development (both according to the test results and the results of the expert assessment by the teacher) is also not related to the initial parameters of readiness for school. Also, there were no differences in improvements in general effects and in specific effects between the classes with experienced and not- so-experienced teacher. So, there are some reasons to believe that the level of the child's actual development does not play a fundamental role for education, which built in accordance with the principles of Cultural Historical Activity Approach.